Higher frequency of mantram repetition practice is associated with enhanced clinical benefits among United States Veterans with posttraumatic stress disorder. Issue 1 (31st December 2022) - Malaktaris, Anne; McLean, Caitlin L.; Mallavarapu, Sheetal; Herbert, Matthew S.; Kelsven, Skylar; Bormann, Jill E.; Lang, Ariel J.
ABSTRACT: Background: There is increasing support for the use of meditation-based treatments for US military Veterans with posttraumatic stress disorder (PTSD). The Mantram Repetition Program (MRP), which is a portable meditative practice that features mindful repetition of a sacred phrase, is associated with significant reductions in PTSD symptom severity. Although regular practice is emphasized in meditation-based interventions, associations between frequency of practice and clinical outcomes are often not reported. Objectives: This study will examine whether the frequency of mantram repetition is associated with greater improvements in clinical outcomes. Methods: Veterans with PTSD participating in MRP ( N  = 160; combined experimental groups from two randomized controlled trials). Participants completed pre- and post-treatment self-report measures of anger and well-being and a clinician-administered interview of PTSD severity (CAPS-IV-TR). Veterans also reported average daily mantram repetition practice at post-treatment. We conducted a series of hierarchal multiple regression analyses. Results: When controlling for race/ethnicity and pre-treatment severity, higher frequency of mantram repetition practice was associated with significantly greater improvements (small effect sizes) in PTSD symptom severity ( F (3, 128) = 6.60, p  < .001, β = .21, p  = .007), trait anger ( F (3, 128) = 31.23, p  <   .001, β = .25, p  < .001), state anger ( F (3, 110)  = 17.62, p  < .001, β = .16, p  = .04), mental health well-being ( F (3, 128) = 28.38, p  < .001, β = .14, p  = .04), and spiritual well-being ( F (3, 127) = 13.15, p  < .001, β = .23, p  = .003), but not physical health well-being. Conclusions: Higher frequency of mantram repetition practice appears to have beneficial effects on clinical outcomes for Veterans with PTSD. Strategies that promote skills practice may be an important target for improving clinical outcomes for meditation-based interventions. HIGHLIGHTS: Higher frequency of meditation practice during Mantram Repetition Program was associated with greater reductions in PTSD symptoms and anger as well as improvements in well-being. Strategies to promote at-home meditation practice may optimize the benefits of MRP.